The experience of adults with visual disabilities in two Brazilian science museums: An exploratory and qualitative study - Fernandes, Mariana Pereira; Norberto Rocha, Jessica (Frontiers in Education, 2022)
In this exploratory and qualitative study, we investigate the experience of two groups of adults with visual disabilities in two science museums in Rio de Janeiro (Brazil). Data collection was performed by recording their visits through a subjective camera placed on the head of one of the visitors. The analysis used three accessibility indicators and barriers as codes. The data reveals that: a) physical accessibility—related to the internal architectural aspects—was well developed; although other elements of this indicator need improvement; b) attitudinal accessibility was present, mostly due to the work and guidance of the museums’ educators; c) communicational accessibility was rare in the museums, either due to a lack of diversified equipment, media or resources both for internal and external communication; d) barriers do exist, mainly because one or more element is missing from the accessibility indicators. This study indicates that the two science museums offer accessibility strategies from the perspective of people with visual disabilities and can provide interactions, learning and science communication for this audience in different levels. However, some barriers in both institutions still need to be improved. Based on our data, results and discussions, museums and their professionals can be inspired, learn and plan an organizational change towards accessibility. Lastly, museums need to be able to learn from people with disabilities.